A novel approach to earlobe reconstruction using the V to Y advancement flap - Laura Allen; Kelti Munroe; S. Mark Taylor (Journal of Otolaryngology - Head and Neck Surgery, 2021)
Abstract Background The V to Y advancement flap offers an excellent option for reconstructing defects of the lobule and adjacent structures of the external ear. We demonstrate its utility for small defects of the earlobe including those extending to the antitragal and conchal bowl regions. To our knowledge use of this technique for earlobe reconstruction has not been reported. Methods A review of the literature was performed on the use of the V to Y flap for earlobe reconstruction. We then described its use in reconstructing lobular defects in 6 patients. All patients had a non-melanoma skin cancer involving the earlobe. All surgeries were performed under local anesthetic at a tertiary care centre in Halifax, Canada. Defects ranged in size from 1.0 to 1.4 cm. All defects were reconstructed with only a V to Y advancement flap. Patient photographs were taken intra-operatively and post-operatively. For all patients, satisfaction of the final aesthetic result was assessed on a 10 point scale in follow-up at 6 months. Results A review of the literature did not reveal any reports of the V to Y flap used in isolation for lobular reconstruction. At our centre from 2018 to 2020, this method was well tolerated under local anesthetic in 6 patients with non-melanoma skin cancers of the earlobe. All patients reported an aesthetically satisfying result at 6 months with scores ranging between 8 and 10. Scarring in all cases was minimal. Conclusion The V to Y advancement flap is a simple technique for reconstructing small defects of the lobule. This method is technically straight-forward, poses minimal risk to the patient, and in our experience, yields a favourable cosmetic outcome. Graphical abstract